Inside Back Cover: A Valence Tautomeric Dinuclear Copper Tetrakisguanidine Complex (Chem. Eur. J. 30/2016). Issue 30 (27th June 2016) - Wiesner, Sven; Wagner, Arne; Kaifer, Elisabeth; Himmel, Hans‐Jörg
Abstract : Valence‐tautomeric dinuclear copper complexes are realized with a bridging redox‐active tetrakisguanidine (GFA) ligand. It is shown that intramolecular electron‐transfer converts a paramagnetic dinuclear Cu II complex with neutral ligand to a diamagnetic dinuclear Cu I complex with dicationic ligand. The electronic structure of the complex is very sensitive to the environment, especially the solvent polarity. In acetone, the two valence‐tautomers are in a temperature‐dependent equilibrium. More information can be found in the Full Paper by H.‐J. Himmel et al. on page 10438 ff.